A nalisis P engembangan P erkebunan Kakao Rakyat di Kabupaten Deli Serdang Provinsi Sumatera Utara - Corry Maharani; Edy Batara Siregar; M.Akbar Siregar (JURNAL AGRICA, 2018)
Cocoa is one of the plantation commodity whose role is quite important for the national economy besides oil palm, rubber and cocoa. Cultivation of cocoa commodity also play a role in encouraging the development of the region, providing jobs and incomes field farmers and agro-industry development. Deli Serdang Regency is one of the centers of cocoa porduksi people in the province of North Sumatra. In 2010, the area under cocoa plantation in Deli Serdang people of 6435.95 ha, 3760.76 production, productivity of 979.21 kg/ha/year and the number of households that looks as much as 9533.00. Deli Serdang is the second largest contributor to the production of cocoa shavings district in North Sumatra province.Based on the analysis, suggests that the cocoa commodity has a number of advantages to the development of the cocoa commodity in Deli Serdang Regency has great prospects and good.Cocoa plantation business people in Deli Serdang gain value, when based on price levels prevailing cocoa farm level (the purchase price at the collector). Financially cocoa plantation business people also deserve to be developed. The results showed that only partially variable parameters cocoa acreage of the previous year (when different variables) that significantly influenced the total area . While the other parameters the real price of cocoa, the real price ofShift differential positive coefficient indicates that the partial commodities are cocoa plantation commodities do not have a competitive advantage in all areas of Deli Serdang. Competitive advantage and cocoa commodity acreage only in districts Sibolangit and Biru Biru. Keywords : cocoa, cocoa plantation folk, shift differentials